Polyvinyl Alcohol-Corn Starch-Lemon Peel Biocomposite Films as Potential Food Packaging - Terzioğlu, Pınar; Parın, Fatma Nur (Manisa Celal Bayar University, 2020)
In this study, novel biocomposite films were prepared by incorporating lemon peel to a polyvinyl alcohol-starch matrix. The influence of the lemon peel content on the structural, mechanical and optical properties of biocomposite films were discussed. The FTIR studies revealed the formation of a strong interaction between lemon peel and polymer matrix. Blending with lemon peel led to an improvement in the UV-light barrier properties of the polyvinyl alcohol-starch films. The incorporation of 1 wt% lemon peel further enhanced the mechanical properties of the films due to good compatibility and bonding between peel particles and polymer matrix. The results showed that lemon by-product has great potential to be evaluated into added-value products for packaging applications.
Keywords: Engineering; Mühendislik